Pengaruh Latihan Permainan Target terhadap Hasil Tendangan ke Gawang (Menembak) di Klub Abhiseva Cabang Kota Bengkulu - Suhendar, I.; N, Ramos; Syaputra, Roni (Educative Sportive, 2025)
This study aims to determine the Effect of Target Game Training on the Results of Kicks Towards the Goal (Shooting) at the Abhiseva Club Branch, Bengkulu City with an Experimental research type. The number of samples is 20 players. The results of the study showed that there was a significant effect of target training on the accuracy of shooting of futsal players at the Abhiseva Branch, Bengkulu City, with a t count of 12.202> t table 2.110, and a significance value of 0.000 <0.05. The percentage increase in shooting of futsal players at the Abhiseva Branch, Bengkulu City after being given target training was 71.04%. t count 12.202 and t table (df 17) 2.110 with a significance value of p of 0.000. Therefore, t count 12.202> t table 2.110, and a significance value of 0.000 <0.05, then these results indicate that there is a significant difference. Thus, the alternative hypothesis (Ha) which states "There is a significant influence of target practice on the shooting accuracy of futsal players at Abhiseva Branch, Bengkulu City" is accepted.